Pengaruh Gaya Belajar Terhadap Hasil Belajar Matematika Siswa Kelas VII SMP N 1 Ampek Angkek Tahun Pelajaran 2022/2023 - Nelly Aprillia; Isnaniah Isnaniah; Emita Gusti (Universitas Pahlawan Tuanku Tambusai, 2022)
Learning style is an important element that is considered in the learning process in order to realize the expected goals of learning mathematics. Learning style refers to the method of learning that students prefer, but there are still many students who do not know and understand their own learning style. The purpose of this study was to determine the effect of learning styles on students' mathematics learning outcomes in class VII SMP N 1 Ampek Angkek in the 2022 academic year. 2023. This type of research is correlational with the nature of Ex post facto research. The data collection technique used in this study was a questionnaire. Data analysis using SPSS. In accordance with the data analysis, it can be concluded: